Effectiveness of Multimedia Nutrition Education on Nutritional Intake in Children Aged 6–24 Months: A Study in Jayapura City - Christin Debora Nabuasa; Mesri Kartika; Grouse Oematan (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: The practice of providing complementary feeding (MP-ASI) for children aged 6–23 months in Indonesia still faces several challenges. According to Presidential Regulation No. 72 of 2021, the national target for 2024 is that 80% of children aged 6–23 months receive appropriate complementary feeding. Monitoring is conducted quarterly, assessing food diversity and the consumption of eggs, fish, or meat. If feeding practices are found lacking, health cadres provide education to mothers or primary caregivers. One major cause of low animal protein intake is the limited knowledge and awareness among mothers about its nutritional importance. Conventional one-way education methods are often ineffective in changing behavior. Therefore, technology-based approaches such as multimedia education are considered more effective due to their visual, auditory, and interactive elements. Objective: To determine the effect of multimedia education on animal-protein-rich complementary feeding on the nutritional intake of children aged 6–24 months in Jayapura City. Methods: A quantitative study using a pre-experimental one group pretest-posttest design was conducted at Hamadi Public Health Center, Jayapura City. The study used total sampling, involving 170 mothers of children aged 6–24 months who visited posyandu in the area. Data were analyzed using the Paired Samples t-test. Results: Multimedia education significantly improved maternal knowledge, attitudes, and the intake of energy, protein, and calcium (p < 0.05). Conclusion: Multimedia-based education on animal-protein-rich complementary feeding effectively enhances knowledge, attitudes, and nutrient intake, supporting IGF-1 hormone production and contributing to stunting reduction efforts.